PERLINDUNGAN HUKUM KHUSUS BAGI ANAK DALAM MASA PANDEMI COVID-19 OLEH DP3A KOTA SEMARANG - Rika Saraswati; Petrus Soerjowinoto; Emanuel Boputra (Jurnal Jendela Hukum, 2023)
Many Indonesian children lost their parents who died because of Covid-19. These children need special protection and have rights that must be fulfilled by governments (either central or local). The aims of this study are to: 1) find out the role of the Semarang City Women's Empowerment and Child Protection Service (DP3A) in carrying out special protection for children whose parents died due to the COVID-19 pandemic and 2) find out the obstacles that are faced by DP3A in implementing this special protection. This research is a non-doctrinal (empirical) legal research and the data used are primary and secondary data. Primary data was obtained through interviews with the Office of Women's Empowerment and Child Protection (DP3A) Semarang City. Secondary data was obtained through literature study related to legal materials according to the research topic. The results of the study demonstrate that the Office of Women's Empowerment and Child Protection (DP3A) has carried out an imperative role in accordance with its duties and functions in accordance with applicable laws and regulations, namely in the field of child protection. The obstacles faced by DP3A are: limited authority and incomprehensive policy.